TECHNOLOGY-BASED COGNITIVE INTERVENTIONS FOR INDIVIDUALS WITH MILD COGNITIVE IMPAIRMENT: A SYSTEMATIC REVIEW. (11th November 2018) - Ge, S; Zhu, Z; Wu, B; McConnell, E S
Abstract: Background: Rapid advances in computing technology have enabled researchers to conduct cognitive interventions with the assistance of technology. This systematic review aims to evaluate the effects of technology-based cognitive training or rehabilitation interventions to improve cognitive function among individuals with MCI. Methods: The following criteria were applied: MCI, empirical studies, and evaluated a technology-based cognitive training or rehabilitation intervention. Twenty-six articles met the criteria. Results: Studies were characterized by considerable variation. The major types of technologies applied included computerized software, tablets, gaming consoles, and virtual reality. Use of technology to adjust the difficulties of tasks based on participants' performance was an important feature. Technology-based cognitive interventions were found to potentially improve global cognitive function, attention, executive function, and memory. Some cognitive interventions improved non-cognitive symptoms such as anxiety, depression, and physical functions. Discussion: Technology-based cognitive training and rehabilitation interventions show promise, but the findings were inconsistent due to the variations in study design.